Geographic variation in abundance and diversity of Acinetobacter baumannii Vieuvirus bacteriophages - Arellano-Maciel, Dafne; Hurtado-Ramírez, Juan Manuel; Camelo-Valera, Laura Carolina; Castillo-Ramírez, Santiago; Reyes, Alejandro; López-Leal, Gamaliel (Frontiers in Microbiology, 2025)
IntroductionProphages play a crucial role in the genomic diversity of Acinetobacter baumannii, contributing to its pathogenicity and adaptation.MethodsIn this study, we induced and sequenced seven prophages from five isolates of A. baumannii. These were analyzed with 967 prophages identified from various isolates worldwide, plus 21 genomes of other phages infecting A. baumannii previously reported in NCBI. To have an overview of the populations of the prophages infecting A. baumannii.ResultsOur analysis revealed 13 major prophage clusters within the analyzed A. baumannii isolates. Notably, prophages belonging to the Vieuvirus genus were the most prevalent. Specifically, Vieuvirus-related phages were frequently identified in isolates from Thailand, Mexico, China, and South Korea, which show the geographic prevalence of A. baumannii prophages.DiscussionThis study highlights the importance of considering geographic factors to fully understand prophage diversity and their significant role in the evolutionary dynamics of A. baumannii.